The San Blas Pluton: An example of Carboniferous plutonism in the Sierras Pampeanas, Argentina - Dahlquist, Juan Andrés (2006)
New geochronological and geochemical data are reported for the San Blas Pluton (SBP), in the northwestern Sierra de Velasco, Sierras Pampeanas, which intrudes Ordovician granitoids developed during the Famatinian orogeny. A precise Carboniferous age of 340±3 Ma is established by U-Pb dating of zircon using a sensitive high-resolution ion microprobe (SHRIMP). The SBP illustrates several petrological and geochemical characteristics of previously reported Carboniferous granitoids in the Sierras Pampeanas. Their generation is consistent with a regional reheating of the crust at approximately 342 Ma, which resulted in the formation of relatively large amounts of granitic melts that were emplaced in higher crustal levels along master fractures (older master shear zones of Lower Paleozoic age). The SBP can be chemically defined as a typical A-type granitoid related to postcollisonal or postorogenic magmatism. Its high REE content and extraordinarily high U and Th concentrations may have economic significance. Many previously published Devonian and Carboniferous K-Ar dates are reset Ordovician ages, but the existence of other Carboniferous bodies in the Sierra de Velasco cannot be discounted until detailed mapping of the whole Sierra is completed.